Association of dipeptidyl peptidase IV polymorphism, serum lipid profile, and coronary artery stenosis in patients with coronary artery disease and type 2 diabetes. Issue 13 (2nd April 2021) - Wang, Zhongsu; Liu, Yang; Wang, Weizong; Qu, Haiyan; Han, Yi; Hou, Yinglong
Abstract : Abstract: Cardiovascular disease (CAD) is a devastating illness, but to date there are limited means of predicting a person's coronary stenosis severity and their prognosis. The study was performed to investigate the relationship between dipeptidyl peptidase 4( DPP4 ) gene polymorphisms and serum lipid profiles, as well as the severity of coronary artery stenosis in patients with CAD and type 2 diabetes (T2DM) for the first time. Herein, 201 patients with CAD and T2DM were enrolled in the Department of Cardiology, Shandong Provincial Qianfoshan Hospital. DPP4 rs3788979 and rs7608798 single nucleotide polymorphisms (SNPs) were genotyped. The general information of all patients was collected, and the associations between DPP4 SNPs and lipid profiles were detected. At the same time, association between SNP polymorphisms and the degree of coronary artery stenosis were analyzed. There was a significant difference in apolipoprotein B (ApoB) levels ( P  = .011) for the rs3788979 polymorphism, while no difference was identified in other blood lipids or with other mutations. SNP mutation of A to G in rs3788979 was associated with a reduced percentage of severe coronary artery stenosis in female patients ( P  = .023) as well as those with nosmoking ( P  = .030), nodrinking ( P  = 0.007), and nocardiovascular family history ( P  = 0.015). G allele of rs3788979 is associated with a reduced ApoB level. Besides, we suggest that G allele in rs3788979 may have a cardioprotective effect and prove to be a useful and specific measure when predicting a patient's coronary stenosis severity if diagnosed with CAD and T2DM. Abstract : Supplemental Digital Content is available in the text